Research progress on circularRNAs in pancreatic cancer: emerging but promising. Issue 9 (2nd September 2019) - Wang, Yi-Zhi; An, Yang; Li, Bing-Qi; Lu, Jun; Guo, Jun-Chao
ABSTRACT: There is currently no diagnostic modality for early-stage pancreatic cancer. Given that adjuvant therapies require further development, the overall survival of pancreatic cancer remains unsatisfactory. Circular RNAs (circRNAs) are a class of noncoding RNAs that play an important role in the progression of many diseases including cancer. CircRNAs mainly bind to microRNAs as microRNA sponges to restore the expression of targeted genes and regulate tumor invasion, metastasis, proliferation, and apoptosis. CircRNAs also play roles in the diagnosis and targeted therapy of tumors. Studies on the mechanisms of action of circRNAs in pancreatic cancer are still in their infancy, but it is anticipated that this field will gradually advance. In this review, we provide a brief introduction to circRNAs from four perspectives: biogenesis, functions, and mechanisms of action, tumor therapy with circRNAs, and circRNAs' roles in pancreatic cancer.